2007
DOI: 10.4103/0019-5278.32460
|View full text |Cite
|
Sign up to set email alerts
|

A study on blood eosinophil level and ventilatory pulmonary function of the workers exposed to storage grain dust

Abstract: The workers engaged in storage grain handling are exposed to storage grain dust and suffer from different respiratory symptoms like, cough wheezing, chest tightness, eye and nasal irritations. It has been reported abroad and the present study results noted that the grain handlers have allergic symptoms like redness of eyes, itching, sneezing, skin rash, breathlessness and decrement of pulmonary function test values. According to their nature of job, the workers of storage grain godowns were divided into four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The range obtained in this study showed that the birds were not anaemic. The high level of eosinophyll in birds fed LDFM and ZDFM could be attributted to destructive type of pulmonary dysfunction as reported by Chattopadhyay et al [22]. Eosinophyll had been reported to play a primary role in detoxification.…”
Section: Resultsmentioning
confidence: 65%
“…The range obtained in this study showed that the birds were not anaemic. The high level of eosinophyll in birds fed LDFM and ZDFM could be attributted to destructive type of pulmonary dysfunction as reported by Chattopadhyay et al [22]. Eosinophyll had been reported to play a primary role in detoxification.…”
Section: Resultsmentioning
confidence: 65%
“…Interleukin (IL)-4, IL-5 and IL-13, plays a vital role in the pathophysiology of eosinophilic airway diseases such as asthma, chronic rhinosinusitis, eosinophilic granulomatosis with polyangiitis and hypereosinophilic syndrome [ 22 ]. Studies have reported the association of blood eosinophils with lower FEV1 in asthmatic patient and a significant decline in FEV1 in COPD patients [ 5 ]. However, there is apaucity on how the eosinophils increases with an increased decline in the lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia in the peripheral blood is typically considered a sign of allergies. Numerous studies have shown a connection between peripheral blood eosinophil levels and pulmonary function impairment [ 5 ]. Quarry employees experience a variety of allergy reactions brought on by dust, which can result in eosinophilia.…”
Section: Introductionmentioning
confidence: 99%
“…Sordrager et al (1995) [20] [21] narrated that the PEFR results were presented according to the blood Eosinophil level. The decrement of mean PEFR level were noticed as the blood levels of eosinophils were gradually increased from 4-10% the maximum number of workers belong to higher Eosinophil levels which is similar to our study.…”
Section: Discussionmentioning
confidence: 99%